Interaction of national cultures in the development of musical life of Transcarpathia in the second half of the 20th century - Onyshchenko, Kateryna M.; Hiha, Stepan P.; Hlukhanych, Olesia M.; Zelinka, Valentyna S.; Vihula, Valentyna I. (Linguistics and Culture Review, 2021)
The development of musical life and culture of Transcarpathia had been influenced by different cultures. Recently, scholars have paid attention to the problem of historical development of the region, as well as the study of the cultural heritage of Transcarpathia. These studies are crucial within the framework of studying various aspects of regional history, which strive to avoid stereotypes, subjectivism, and other factors. The purpose of this study is to identify different cultural influences on Transcarpathian musical life in the second half of the 20th century. The research methodology is based on such theoretical methods as synthesis and analysis of information, as well as the historical method. Cultural studies and socio-cultural approaches were used. In addition, the theoretical analysis of academic literature was conducted in this study. The multiculturalism of Transcarpathia in the middle and at the end of the 20th century was considered in this study. It was determined that in the second half of the 20th century the leading ethnic groups in the region, who were Ukrainians, Hungarians and Romanians, coexisted within different small territories and zones. Small groups of Russians, Germans, Slovaks, Jews and Roma have also lived among them.